Hubungan Antara Konsep Baik dan Buruk Dalam Ilmu Kalam Dengan Konsep Maslahat Dalam Hukum Islam - Fathurrahman Djamil (Al-Jami'ah: Journal of Islamic Studies, 1999)
There is a hypothesis that a theological school belongs to a Muslim influences his or her thought in uṣūl al-fiqh (foundation of "Islamic jurisprudence). This paper will focus on Mu'tazila and Asy'ariya. Mu'tazila concept on 'aql or Reason is clear that reason can distinguish between good and bad. This concept is a result of their interest in philosophy that may influence their thought. Therefore, the Mu'tazilite believe in the ability of reason in understanding everything and it brings them to a statement "reason before law", which means reason should stay before the"syara" or law. For this reason, they agree that before the existence of law, a reasonful person can distinguish between good and bad. One of Mu'tazila principles is adala (God justice), that one of its interpretations is that God does not wish the bad. As a result, Mu'tazila believe that. God created all things based on purpose and wisdom. From this point, there seems to be a relation between their teachings and their theories on " uṣūl al-fiqh” When there is a conflict between naṣ and reason, they take reason before naṣ. Furthermore, they believe that God created the creatures on the basis of purpose, and so what happens to His legislation. This concept has a direct influence to the concept of maṣlaha that becomes illa in legislation. Different from Mu'tazila, Ahl al-sunnah wal-Jamā'a sees that good and bad cannot be understood by reason itself. In addition they say that God created all creatures not on the basis of purpose, and also God desires good and bad. These principles relate to their theories on uṣūl al-fiqh; e.q. when a conflict between naṣ and reason emerges, they give priority to nap. They neglect maṣlaha in their canonical thought. Even though, the hypothesis of the relation between theological unrestrictedly. That happens to Al-Juwayni and al-Razi who were Asy'arites but had different thoughts in uṣūl al-fiqh.